IN OUR CULTURE PATH, AND IN THIS CONTEXT THE SYMBOLIC ANALYSIS OF THE POEM CALLED “I AM ON A LONG AND NARROW PATH” - Şimşek, Esma (TÜRKİYE TEMEL BİLİMLER ARAŞTIRMA VAKFI, 2017)
'' Path '' in pure meaning, '' the distance to go beyond from one place to another '' , has many metaphorical meanings such as ; behavior, attitude, aim, good luck, purpose, adopted policies, systems, style, procedures, vision of life, life time, earth, morality way of life, approach, etc... Path might mean hope, joy, tears and getting apart. Path, which makes far near, connecting longing,  eliminating the barriers, is the cause of negativity of the experiences throughout the time. Path, which has an important place - especially in the field of literature- literally and figuratively in our culture, in a sense symbolizes life as well. One first seeing the light of day is yet to begin and aware of nothing. The experinces he lives through shapes and puts him in a certain pattern just like the words describing, '' we were inexperienced, then became knowledgeable and were in blaze of love ''. And here, in the poem of Asik (minstrel) Veysel, '' õ am on a long and narrow path'' , in our day, it is performed as Turkish Anatolia turku/ song  form- path has been symbolically used for the earth and life. Seeing the light of day , human beings keep running after a  target. Considering earth as a place of test, people are always in search of something, as it says in the verse, '' I keeep going day and night''. Lifelong, in a world of believed to be temporary, but opening to another world just like living through , '' a two- door inn'', people walk on and on for the sake of ripening their own personality. In this article, after briefly describing the place and importance of the path in our culture, Asik Veysel's mentioned poem and some others with '' Path'' will be evaluated in terms of symbolic expressions.

Kelime anlamı; “bir yerden bir yere gitmek için aşılan uzaklık” olan “yol”un; davranış, tutum, gaye, uğur, maksat, uyulan ilke, sistem, usul, tarz, hayat görüşü, ömür, dünya, ahlâk, gidiş veya davranış biçimi vs. gibi birçok mecazî anlamı vardır. Yol, kişiye göre umuttur, sevinçtir, gözyaşıdır, ayrılıktır. Uzakları yakın eden, hasretleri kavuşturan, engelleri aradan kaldıran yol, bazı zamanlar da yaşanılan olumsuzlukların sebebidir. Gerçek ve mecazî anlamlarıyla kültürümüzde, özellikle de halk edebiyatı alanında önemli bir yere sahip olan yol, bir anlamda hayatı da sembolize eder. Hayata gözlerini yeni açan birey, henüz yolun başındadır ve hiçbir şeyden haberdar değildir. Yaşadığı olaylar onu tıpkı; “hamdık, piştik, yandık” sözlerinde olduğu olgunlaştırıp belli bir kalıba sokar. İşte, Âşık Veysel’in, bugün türkü/şarkı olarak da bestelenip söylenen; “Uzun ince bir yoldayım” adlı şiirinde de yol sembolik olarak dünya/hayat yerine kullanılmıştır. Dünyaya gelen insan, ömrü boyunca bir hedef peşinde koşup durur. Bir sınav yeri olarak değerlendirebileceğimiz dünyada; “Gidiyorum gündüz gece” şeklindeki mısradan da anlaşılacağı üzere hep bir arayış içindedir. Kişi, ömrü boyunca “iki kapılı bir han” misali geçici ama başka bir âleme açılışı olduğuna inanılan dünyada; kendi benini olgunlaştırma adına, durup dinlenmeden yürür.Bu yazıda, yolun kültürümüzdeki yeri ve önemi kısaca anlatıldıktan sonra Âşık Veysel’in adı geçen şiiri ve diğer şiirlerindeki “yol” ile ilgili ifadeleri sembolik açıdan değerlendirilmeye çalışılacaktır.
KÜLTÜRÜMÜZDE YOL VE BU BAĞLAMDA "UZUN İNCE BİR YOLDAYIM" ADLI ŞİİRİN SEMBOLİK ÇÖZÜMLEMESİ